Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am having a difficult time understanding where I went wrong with the following: $$\begin{matrix}4x-y = 1 \\ 2x+3y = 3 \end{matrix} $$ $$\begin{matrix}4x-y = -3 \\ 2x+3y = 3 \end{matrix} $$

I found the inverse of the common coefficient matrix of the systems: $$A^{-1} \begin{cases} \frac3{14}, \frac1{14} \\ \\ -\frac17, \frac27 \end{cases} $$

The issue is this question: Find the solutions to the two systems by using the inverse, i.e. by evaluating $A^{-1}B$ where $B$ represents the right hand side (i.e. $B = \begin{bmatrix}1 \\ 3 \end{bmatrix}$ for system (a) and $B = \begin{bmatrix}-3 \\ 3 \end{bmatrix}$ for system (b)).

Now whatever I find for x and y for both solutions keep coming as wrong. I am thinking, I might of read the question wrongly....I am using the negative values to find the x and y. Not too sure how to go at this now...

share|cite|improve this question
up vote 1 down vote accepted

$A^{-1} = \frac{1}{14}\begin{bmatrix} 3 & 1 \\ -2 & 4\end{bmatrix}$.

$A^{-1} \binom{1}{3} = \frac{1}{14} \binom{6}{10} = \frac{1}{7} \binom{3}{5}$.

$A^{-1} \binom{-3}{3} = \frac{1}{14} \binom{-6}{18} = \frac{1}{7} \binom{-3}{9}$.

share|cite|improve this answer

You can rewrite the given equations by defining the coefficient matrix A, variable matrix X, and constant matrix B as

$$ A =\left[\begin{matrix} 4&-1\\ 2&3 \end{matrix}\right] \\ X = \left[\begin{matrix} x\\ y \end{matrix}\right] \\ B=\left[\begin{matrix} 1&-3\\ 3&3 \end{matrix}\right] $$

Then, your two systems can be represented simply by $$ AX = B, $$ and to solve the system, you can left multiply both sides by the inverse of A, which is

$$ A^{-1} = \left[\begin{matrix} \frac {3}{14}&\frac {1}{14}\\ -\frac {1}{7}&\frac {2}{7} \end{matrix}\right] $$

This gives $$ A^{-1}AX=A^{-1}B\\ X = \left[\begin{matrix} \frac {3}{7}&\frac {-3}{7}\\ -\frac {5}{7}&\frac {9}{7} \end{matrix}\right] $$ So $(x,y) = (\frac3 7,\frac5 7)$ for the first equation, and $(x,y) = (-\frac37,\frac97)$ for the second.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.